2H-chromene and 7H-furo-chromene derivatives selectively inhibit tumour associated human carbonic anhydrase IX and XII isoforms - Lisa Sequeira; Simona Distinto; Rita Meleddu; Marco Gaspari; Andrea Angeli; Filippo Cottiglia; Daniela Secci; Alessia Onali; Erica Sanna; Fernanda Borges; Eugenio Uriarte; Stefano Alcaro; et al. (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
Tumour associated carbonic anhydrases (CAs) IX and XII have been recognised as potential targets for the treatment of hypoxic tumours. Therefore, considering the high pharmacological potential of the chromene scaffold as selective ligand of the IX and XII isoforms, two libraries of compounds, namely 2H-chromene and 7H-furo-chromene derivatives, with diverse substitution patterns were designed and synthesised. The structure of the newly synthesised compounds was characterised and their inhibitory potency and selectivity towards human CA off target isoforms I, II and cancer-associated CA isoforms IX and XII were evaluated. Most of the compounds inhibit CA isoforms IX and XII with no activity against the I and II isozymes. Thus, while the potency was influenced by the substitution pattern along the chromene scaffold, the selectivity was conserved along the series, confirming the high potential of both 2H-chromene and 7H-furo-chromene scaffolds for the design of isozyme selective inhibitors.